REPETITIVE DNA SEQUENCES IN THE GENOMES OF PLANTS - A. B. Shcherban (Вавиловский журнал генетики и селекции)
The main classes of repetitive DNA sequences, including coding (rRNA genes) and non-coding sequences (tandem and dispersed repeats) are characterized. Emphasis is placed on their special role in the formation of the structural and functional organization of the genomes of higher plants and in the support of their higher genetic variation, as compared to animal genomes, at the levels of individual sequences and of the whole genome.